ANALISIS PENERAPAN MANAJEMEN RISIKO OPERASIONAL PADA USAHA MIKRO KECIL DAN MENENGAH SEKTOR KULINER: STUDI KASUS WARUNG ECCO ROSO KEDIRI - Margaretha Yulianti; Elisabeth Elsa; Fransiska Sulistia; Yusni Nona Wohen; Tresia Winata Dua Dori (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Risk management is a crucial aspect of business sustainability, especially for Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector which face various business environment uncertainties. This study aims to analyze the implementation of operational risk management at Warung Ecco Roso Kediri, covering the processes of risk identification, analysis, evaluation, control, and monitoring applied by the business owner. This research employed a qualitative descriptive method with a case study approach, using in-depth interviews and field observation for data collection. The results showed that the implementation of operational risk management at Warung Ecco Roso Kediri has been carried out across all process stages, yet it remains simple, informal, and based on the owner’s experience without systematic documentation. The main identified risks include raw material risks, market demand risks, business competition risks, as well as service and hygiene risks. The control strategies implemented focus on maintaining product quality, operational efficiency, and price adjustment. Although the applied system is not formally structured, these risk management practices are considered effective in maintaining business stability and continuity. This study recommends the development of Standard Operating Procedures (SOPs), risk documentation, and the use of a risk matrix to improve risk management effectiveness in the future.